The Median Effective Analgesic Concentration of Ropivacaine in Sciatic Nerve Block Guided by Ultrasound After Arthroscopic Anterior Cruciate Ligament Reconstruction: A Double-Blind Up-Down Concentration-Finding Study - Xu, Cheng; Gu, Fei; Wang, Chengyu; Liu, Yang; Chen, Rui; Zhou, Quanhong; Lu, Jie (Frontiers in Medicine, 2022)
Background: The median effective concentration of ropivacaine of ultrasound guid-ed sciatic nerve block required for effective postoperative analgesia after arthro-scopic anterior cruciate ligament reconstruction has not yet been determined. This study was to explore the median effective analgesic concentration of 20mL ropiva-caine required to produce a successful sciatic nerve block for postoperative anesthe-sia. Method: A total of 29 patients underwent elective arthroscopic anterior cruciate lig-ament reconstruction were enrolled in the study. All the patients received 20ml 0.2% ropivacaine for femoral nerve block for the operation. A concentration of 20mL ropivacaine administered for the sciatic nerve was determined using the up-and-down sequential. The starting concentration was 0.2% in the first patient, the next patient would receive decremented 0.025% of ropivacaine if the prior patient’s postoperative visual analog pain score was less than 4 in the initial 8h. Otherwise, the following patient would received an incremental of 0.025% of ropivacaine. The ana-lytic techniques of linear, linear-logarithmic, exponential regressions and centered isotonic regression were used to determine the EC50 of ropivacaine and the residual standard errors were calculated for the comparison of “goodness of fit” among the different models. Results: The concentration of ropivacaine administered ranged from 0.1% to 0.2%. The ED50 (95% confidence interval) from 4 different statistical approaches (linear, linear-logarithmic, exponential regressions and centred isotonic regression) were 0.129% (0.103%, 0.359%), 0.142% (0.112%, 0.347%), 0.113% (0.108%, 0.343%), and 0.115%, respectively. Among all of the 4 models, the exponential regression had the least residual standard error (0.2243). Conclusion: The EC50 derived from four statistical models for 20ml ropivacaine in ultrasound-guided sciatic nerve block for postoperative analgesia was distributed in a narrow range of 0.113%–0.142%, and the exponential regression was the model to best match the study data.